Guidelines of Diagnostics and Treatment of Acute Left-Sided Colonic Diverticulitis - Andeweg, Caroline S.; Mulder, Irene M.; Felt-Bersma, Richelle J.F.; Verbon, Annelies; van der Wilt, Gert Jan; van Goor, Harry; Lange, Johan F.; Stoker, Jaap; Boermeester, Marja A.; Bleichrodt, Robert P. (Digestive surgery, 2013)
Background: The incidence of acute left-sided colonic diverticulitis (ACD) is increasing in the Western world. To improve the quality of patient care, a guideline for diagnosis and treatment of diverticulitis is needed. Methods: A multidisciplinary working group, representing experts of relevant specialties, was involved in the guideline development. A systematic literature search was conducted to collect scientific evidence on epidemiology, classification, diagnostics and treatment of diverticulitis. Literature was assessed using the classification system according to an evidence-based guideline development method, and levels of evidence of the conclusions were assigned to each topic. Final recommendations were given, taking into account the level of evidence of the conclusions and other relevant considerations such as patient preferences, costs and availability of facilities. Results: The natural history of diverticulitis is usually mild and treatment is mostly conservative. Although younger patients have a higher risk of recurrent disease, a higher risk of complications compared to older patients was not found. In general, the clinical diagnosis of ACD is not accurate enough and therefore imaging is indicated. The triad of pain in the lower left abdomen on physical examination, the absence of vomiting and a C-reactive protein >50 mg/l has a high predictive value to diagnose ACD. If this triad is present and there are no signs of complicated disease, patients may be withheld from further imaging. If imaging is indicated, conditional computed tomography, only after a negative or inconclusive ultrasound, gives the best results. There is no indication for routine endoscopic examination after an episode of diverticulitis. There is no evidence for the routine administration of antibiotics in patients with clinically mild uncomplicated diverticulitis. Treatment of pericolic or pelvic abscesses can initially be treated with antibiotic therapy or combined with percutaneous drainage. If this treatment fails, surgical drainage is required. Patients with a perforated ACD resulting in peritonitis should undergo an emergency operation. There is an ongoing debate about the optimal surgical strategy. Conclusion: Scientific evidence is scarce for some aspects of ACD treatment (e.g. natural history of ACD, ACD in special patient groups, prevention of ACD, treatment of uncomplicated ACD and medical treatment of recurrent ACD), leading to treatment being guided by the surgeon's personal preference. Other aspects of the management of patients with ACD have been more thoroughly researched (e.g. imaging techniques, treatment of complicated ACD and elective surgery of ACD). This guideline of the diagnostics and treatment of ACD can be used as a reference for clinicians who treat patients with ACD.